Prosocial behavior among high school students: The role of spirituality and self-regulation - Adinda Dwi Putri; Fuad Nashori (Personifikasi: Jurnal Ilmu Psikologi, 2026)
The aim of this research is to determine the relationship between spirituality, self-regulation, and prosocial behavior in high school students. The scales used in this research were Eisenberg and Mussen’s Adolescent Prosocial Scale, adapted by Arifah and Nurina, and the Values in Action Inventory of Strengths (VIA-IS), compiled by Peterson and Seligman and modified by Oriza and Nurwianti, to measure spirituality and self-regulation. Using purposive sampling, the participants in this research were 183 high school students in Purwakarta. This research shows a positive correlation among spirituality, self-regulation, and prosocial behavior (p=0.000, p0.05). The higher the levels of spirituality and self-regulation, the higher the level of prosocial behavior. This study clarifies inconsistent findings by demonstrating that self-regulation predicts prosocial behavior more strongly than spirituality.  The implication of the results of this research is that schools need to design programs to foster spirituality and self-regulation in students, so that students can demonstrate prosocial behavior in their daily lives.